Pro ADO.NET 2.0 - Malikrdrac, Sahil (Apress, 2012)
Mission control to reader . . . you are now nearing the ADO.NET planet in the .NET solar system of the Microsoft technology galaxy.Make sure no architectural mistake alien eats you up for dinnerT